A digital agricultural extension platform to boost adoption of improved technologies and practices in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2019)
In 2019, the Government of Ethiopia launched "Digitalizing Agricultural Advisory Services", a country-wide project aiming at developing a digital platform to deliver location and time-specific advice to farmers. IFPRI's results on the benefits of Digital Green's video-mediated approach to agricultural extension strongly influenced this investment.